Legal framework for public participation in flood risk mapping: A comparative study of the responses of different European Member States to some requirements of the Floods Directive - Herwig Unnerstall (Helmholtz-Zentrum für Umweltforschung (UFZ), 2010)
This report is a comparative study of the current legal situation in relation to the forth-coming implementation of the Floods Directive in selected EU Member States, focusing on the question of whether these states incorporate public participation into the process of flood risk mapping and, if so, in what form. The comparison also considers current administrative practices.
Keywords: 330; Überschwemmung; Risikomanagement; EU-Recht; Partizipation; Deutschland; Österreich; Großbritannien